Community Treatment Orders use Among Persons With a First Episode of Psychosis in Quebec. (February 2023) - Nguyen, Minh Thi; Sicotte, Roxanne; Pires De Oliveira Padilha, Paula; Abdel-Baki, Amal
Objectives: Specialized early intervention for psychosis can reduce the duration of untreated psychosis and improve clinical and functional outcomes. However, poor adherence to treatment is frequent. The literature on community treatment orders (CTOs) use in first-episode psychosis (FEP) as a means to improve treatment adherence is limited. In the context of early intervention for psychosis services (EIS), this study aims to describe (1) the frequency of CTOs utilisation, (2) the trend of CTOs use over time, (3) the timing and reasons for requesting CTOs and (4) the baseline characteristics of FEP patients on CTOs compared to those who were not. Method: A 5-year prospective longitudinal study describing the use of CTOs among persons with FEP admitted to two urban EIS in Montreal, Quebec, from 2005 to 2013. At admission, and then annually for 5 years, CTOs data were collected through chart review. Baseline characteristics, assessed by patient interviews, standardized questionnaires and chart review, included socio-demographic data, illness severity, functioning and alcohol and substance use. Descriptive analyses were performed, and FEP patients on CTOs during follow-up and those who were not were compared using analyses of variance, chi-square test and multivariate logistic regression. Results: Among 567 FEP patients, 19.2% were placed on CTOs. The main reasons for requesting CTOs were to prevent further deterioration in mental state, social functioning, harmful behaviours to self and others and homelessness. FEP patients on CTOs had poorer premorbid and baseline functioning, more severe symptoms and social dysfunction at admission, including legal problems and homelessness. Conclusions: CTOs can be a tool to improve adherence to treatment, which is crucial for relapse prevention in FEP. However, since it is a coercive method that limits a person's fundamental rights, further research is warranted to assess its impact on patients' lives, clinical and functional outcomes, as well as patients' and carers' perception.